Hubungan Antara Otitis Media Supuratif Kronik Dengan Gangguan Pendengaran Di Poliklinik Tht Rs Royal Prima Medan - Zendrato, Ester Junita; Tambunan, Andika Zayani; Rusip, Gusbakti (Syntax Corporation, 2025)
Chronic Suppurative Otitis Media (CSOM) is a chronic middle ear infection characterized by tympanic membrane perforation and continuous or recurrent ear discharge. This condition can cause hearing loss if not properly treated. This study aims to determine the relationship between Chronic Suppurative Otitis Media and hearing loss in patients at the ENT Clinic of Royal Prima Hospital Medan. This research is an analytical observational study with a cross-sectional design conducted on 32 patients who met the inclusion criteria. Data were obtained from medical records and pure-tone audiometry results to determine the type and degree of hearing loss. The results showed that most patients experienced conductive hearing loss, with 23 individuals (71.9%), and the most common degree of hearing loss found was mild hearing loss, with 15 individuals (46.9%). The results of the Chi-Square test showed a significant relationship between CSOM and hearing loss (p = 0.012). The recommendation of this study emphasizes the importance of early detection, consulting a doctor for further management, and receiving adequate treatment, as hearing loss can affect communication ability and the quality of life of the sufferers.